A Case of Neuromuscular Electrical Stimulation for Childhood Stroke Hyperkinesis: A Brief Report. (17th August 2020) - Metzler, Megan J.; Cole, Lauran; Kirton, Adam
ABSTRACT: Aim: Some conditions within specific populations are so rare rigorous evidence is unavailable. Childhood hyperkinesis is one example, yet presents an opportunity to examine sensation's contribution to motor function. Methods: The patient experienced functional difficulty from hyperkinesis as a result of childhood stroke. Home-based passive neuromuscular electrical stimulation (NMES) was implemented an hour/day, six days/week, over 6 weeks (36 hours). Clinical and robotic measures (Assisting Hand Assessment, Box and Block Test, Jebsen Taylor Test of Hand Function, Kinarm) were administered before and after the intervention and at 9 months. Results: NMES was feasible and well tolerated. Clinically important gains of arm function were maintained at 9 months. Robotic measures showed improved hyperkinesis, namely reduced movement segmentation and improved target approximation, in addition to improved proprioceptive function after NMES. Conclusion: This case study illustrates the use of NMES within a previously unexplored population and highlights the potential importance of sensory systems to motor gains.